2018
DOI: 10.1007/s10653-018-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluoridation and county-level secondary bone cancer among cancer patients 18 years or older in New York State

Abstract: The decision whether to fluoridate drinking water continues to be controversial in some communities. Dental and skeletal fluorosis in response to chronic fluoride overexposure are cited as reasons to avoid community water fluoridation in spite of evidence of the oral and skeletal health benefits fluoridation confers. Community fluoridation of ~ 1 mg/L fluoride has not been found to be associated with primary bone cancer but is associated with improved bone strength. No studies have examined fluoride exposure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…All sites 3 [10,11,19] Digestive organs 4 [10,11,20,21] Respiratory organs 4 [10,11,19,20] Urinary organs 4 [10,11,19,20] Hormonal and/or reproductive organs 4 [10,11,19,20] Bone 8 [10,11,[13][14][15][16][17]22] Brain and nerves 3 [10,11,15] Blood and lymph 3 [11,15,19] Lip and skin 1 [11] Eye cancer 1 [18] *Some articles investigated more than 1 cancer site…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…All sites 3 [10,11,19] Digestive organs 4 [10,11,20,21] Respiratory organs 4 [10,11,19,20] Urinary organs 4 [10,11,19,20] Hormonal and/or reproductive organs 4 [10,11,19,20] Bone 8 [10,11,[13][14][15][16][17]22] Brain and nerves 3 [10,11,15] Blood and lymph 3 [11,15,19] Lip and skin 1 [11] Eye cancer 1 [18] *Some articles investigated more than 1 cancer site…”
Section: Referencesmentioning
confidence: 99%
“…[9] For example, there is an ongoing debate in the scientific community about the role of fluoridated water in cancer development in humans; and different epidemiological studies had been conducted to establish or refute this relationship. [10][11][12][13][14][15][16][17][18][19][20][21][22] While some studies reported no relationship between fluoridated water consumption and cancer occurrence, others reported a direct or an inverse relationship between them. [10][11][12][13][14][15][16][17][18][19][20][21][22] Despite the significant quantity of epidemiological studies that had investigated the relationships between community water fluoridation and human cancers, no known study has the quantity of the existing epidemiological evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, long-time ingestion of high concentrations of fluoride causes many health problems such as dental and skeletal fluorosis (Ali et al, 2016), lower intelligence of children (Green et al, 2019) and bone cancer (Crnosija et al, 2019). The World Health Organization (WHO) recommends a fluoride guideline value in drinking water of 1.5 mg/L (World Health Organization, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns that excessive fluoridation of water can be carcinogenic, increasing incidence of cancer, particularly osteosarcoma in boys (5). Yet, population studies have shown no link between fluoride consumption and cancer incidence (6)(7)(8). This topic remains controversial with strong opposing views.…”
Section: Introductionmentioning
confidence: 99%